Transformation of Inheritance Rights in Balinese Customary Land - Putu Diana Prisilia Eka Trisna; I Nyoman Sujana; Putu Ayu Sriasih Wesna (Jurnal Smart Hukum (JSH), 2026)
This study examines the transformation of inheritance rights in Balinese customary land within the context of customary and national legal systems. The research addresses legal issues arising from changes in customary membership, which may alter or terminate inheritance rights over communal land. Employing a normative legal research method with statutory and conceptual approaches, this study analyzes the interaction between customary norms and national agrarian law. The findings reveal that inheritance rights over customary land are inherently linked to social-religious obligations and active membership within the customary community, resulting in the transformation or loss of such rights when these obligations are no longer fulfilled. Furthermore, the study identifies a normative tension between the communal character of customary law and the individualistic principles of national inheritance law, leading to legal uncertainty. The novelty of this research lies in its integrative analysis of inheritance transformation through the lens of legal pluralism, emphasizing the need for harmonization between legal systems. The study concludes that clearer legal recognition and contextual legal approaches are necessary to ensure certainty and substantive justice in customary inheritance disputes. Future research is recommended to explore empirical perspectives and judicial practices in resolving similar disputes.